The DNAJ gene family in yerba mate (Ilex paraguariensis): genome-wide identification, structural characterization, orthology based classification and expression analysis - Aguilera, Patricia Mabel; Debat, Humberto Julio; Castrillo, María Lorena; Bich, Gustavo Angel; Grabiele, Mauro (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2023)
Dry leaves and twigs of yerba mate are widely infusion-consumed in southern Southamerica. Endemic and adapted to the Atlantic Forest, its extensive full-sun monoculture links to diverse biotic (pest, pathogens) and abiotic stresses (solar radiation, drought), impacting its productivity, ecology and socioeconomic niche. We focused in comprehensively characterize the DNAJ gene family in yerba mate to predict its possible roles on development and diverse stress responses to further assist crop manage. Our results suggest that yerba mate DNAJ proteins account 140 diverse members of six structural types displaying potential variable roles in protein homeostasis control. We were able to classify them into 51 distinct orthology groups, in agreement to Arabidopsis, and performed translational genomics of function, localization, expression and stress responsiveness data. Genome mapping and expression analysis indicated that yerba mate DNAJ genes differ in expression, nucleotide composition, length and exon-intron structure. Intronless or few introns genes -linked to rapid stress response- accounted 85 DNAJs. Promoters of DNAJ genes harbored a 73.2% of cis-acting regulatory elements involved in response to diverse stresses, hormones and light, simultaneously. We hypothesize that yerba mate DNAJs assist to plant survival during multiple stresses linked to current dominant agroecosystem but promote its growth under shade.